Th1 and Th2 cytokine profile in women with unexplained infertility - Yahya, Nurul Khaiza
Unexplained infertility, referring to the failure to conceive of a couple in whom no definite cause of infertility can be found despite a complete infertility evaluation. The incidence of unexplained infertility was reported to be approximately 15% - 17% among the infertile couples. The etiology is still remain unknown, however, cytokine profile ofT helper 1 (Th 1) subsets such as interferon gamma (IFN y) and interleukin 12 (IL 12) might play a role in the cause of unexplained infertility. OBJECTIVES This study was designed to measure the level of four different cytokines [( Th I consists of IFN y, IL 12 and T helper 2 (Th 2) consists of interleukin 4 (IL 4), interleukin 13 (IL I3)] in unexplained infertile and fertile subjects in order to determine the role of these cytokines in unexplained infertility. Hence this study is aimed to determine the distribution of cytokine profile, the mean differences of cytokine concentration between unexplained infertile and fertile groups as well as the association of other factors such as age, body mass index (BMI), occupation and education level toward unexplained infertility. METHODOLOGY A cross sectional study was done from January to December 2005. A Hundred respondents were enrolled, of whom 50 women had unexplained infertility and 50 women with normal fertility. In this study, women with unexplained infertility were chosen from Infertility Clinic, Hospital Universiti Sains Malaysia (HUSM) and Hospital Raja Perempuan Zainab II (HRPZ II) due to limited sample and fertile women were gathered from HUSM. All patients who fulfilled the inclusion and exclusion criteria and gave written consent were recruited for this study. Interviewer guided questionnaire was administered to gather patient's information. Blood was taken and serum was separated and alii quoted for the measurement of four cytokines, which are IL 12, IFN y, IL 4 and IL I 3 using the Enzyme Linked Immunosorbent Assay (ELISA) assay. RESULT We found that in univariate analysis the median (interquartile range) concentration of IL I 2 and IFN y in unexplained infertility were 7.6 (I 0.04), and 8.0 (16.6 I) respectively. In addition, the mean differences (95% Cl) ofiL 12 and IFN y were -14.44, and -19.11 with p value of 0.003, and 0.015. Therefore, the mean concentration of IL 12 and IFN y was significantly different between unexplained infertile and fertile groups. After~controlling the variables in multiple logistic regression, the significant factors associated with unexplained infertility were IL I 2 (OR: 1.305 ; 95% CI: I. I 19, I .522; p = 0.00 I) and IFN 'Y (OR: 1.291; 95% CI: 1.057, 1.576;p = O.OI2). On the other hand, other variables such as IL 4, IL I3, age, BMI, occupation and education level were found to have no significant association with unexplained infertility. CONCLUSION This study showed that certain interleukins can play a role in infertility. Increase serum level of IL I2 and IFN y might be one of an underlying factor contributing to the infertility by means of skewing towards Th I which is responsible for cellular mediated immunity.